Consensus based recommendations for the management of post-COVID long-term sequelae (Long COVID): a regional perspective - Majid AlShamrani; Fayssal Farahat; Abdullah Assiri; Sami AlHajjar; Ali Albarrak; Hashem AlHashemi; Mohammed AlZunitan; Meshal AlAqeel; Sami AlYami; Ziad A. Memish; Ziad A. Memish; Ziad A. Memish (Frontiers in Medicine)
Background and objectiveThe coronavirus disease 2019 (COVID-19) pandemic marks the biggest public health emergency of the 21st century. The long-term health issues linked to COVID-19, also known as Long COVID, pose a great challenge to patients and society. This article aims to highlight the current unmet clinical needs and present expert recommendations for region-specific assessment and management of Long COVID.MethodsA secondary desk research was performed focusing on global and regional guidelines for the assessment and management of Long COVID. The observations from the desk research form the foundation for the consensus statements. Additionally, an expert panel consisting of 10 consultant physicians from related specialties reviewed these guidelines and literature in advisory board meetings to identify unmet needs, bridge clinical gaps, and develop recommendations for the evaluation and management of Long COVID.ResultsThe expert recommendation statements were drafted based on overarching principles for the clinical assessment and management of Long COVID. The overarching principles used a targeted, multidisciplinary approach, and collaboration between multiple specialties of healthcare. The panel also highlighted the value of holistic care for the management of Long COVID.ConclusionLong COVID is a major public health challenge. These expert recommendations are expected to guide healthcare professionals in their clinical decision-making for the assessment, management, and appropriate rehabilitation of patients with Long COVID.